2019
DOI: 10.3390/w11040783
|View full text |Cite
|
Sign up to set email alerts
|

Sizing of Domestic Rainwater Harvesting Systems Using Economic Performance Indicators to Support Water Supply Systems

Abstract: This paper presents a monitoring-based investigation of rainwater collection systems using economic performance indicators in a group of households with nonconventional end-uses for rainwater that are not traditionally associated with rainwater supply. The monitored data for five household rainwater tank systems were analysed in two stages. For the first stage, the data was empirically analysed to develop a method to predict effective roof catchment areas. For the second stage, the effective roof catchment are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…In Philadelphia, USA, it was observed that the most common roof areas were in the range of 50-60 m 2 [12]. In New York, most houses had roof areas between 80-90 m 2 [12]. In this study, the average roof area of 57,946 houses was 101.6 m 2 .…”
Section: Daily Rainfallmentioning
confidence: 45%
See 3 more Smart Citations
“…In Philadelphia, USA, it was observed that the most common roof areas were in the range of 50-60 m 2 [12]. In New York, most houses had roof areas between 80-90 m 2 [12]. In this study, the average roof area of 57,946 houses was 101.6 m 2 .…”
Section: Daily Rainfallmentioning
confidence: 45%
“…Regarding the rest, the relative frequency percentage was between 0-5%. In Philadelphia, USA, it was observed that the most common roof areas were in the range of 50-60 m 2 [12]. In New York, most houses had roof areas between 80-90 m 2 [12].…”
Section: Daily Rainfallmentioning
confidence: 99%
See 2 more Smart Citations
“…A typical RWH system consists of the concentration, collection, and storage of rainwater for use on site and reduction of drinking water consumption from centrally supplied sources. In urban areas rainwater can be collected from impervious surfaces such as roofs, terraces or courtyards [24]. Harvested water is stored in above or underground tanks with capacities designed according to water demand [6,25].…”
Section: Introductionmentioning
confidence: 99%